[Say's Law and Walras' Law Once More]: Reply - Mishan, E. J. (Quarterly Journal of Economics, 1964)
Journal Article Say's Law and Walras' Law Once More: Reply Get access E. J. Mishan E. J. Mishan London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 3, August 1964, Pages 484–487, https://doi.org/10.2307/1879480 Published: 01 August 1964